THE CORRELATION BETWEEN CONCEPT SENTENCE METHOD TO STUDENTS’ WRITING SKILL AT THE SEVENTH CLASS OF MTs AL-KHAIRIYAH PEKALONGAN – CILEGON ACADEMIC YEAR 2013/2014 - Fitri Ningsih; Ahmad Yanuar Syauki (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Banten, 2013)
The research was intended to find out the correlation between Concept Sentence Method To Students’ Writing Skill at the Seventh Class of MTs Al-Khairiyah Pekalongan Cilegon Academic Year 2013/2014. The kind of research is correlation with quatitative approach. The population in this research were the students of MTs Al-Khairiyah Pekalongan – Cilegon as many as 88 students. Sampling that had been used is random sampling by using Slovin formula. Data collecting method was used by giving questionaire to get the data from Concept Sentence Method and the test to get the data from Students’ Writing Skill. Hypothesis was examined by using SPSS statistical Calculation by calculating normality, homogeneity, analysis coefcience correlation and regression. Data used to examined hypothesis are concept sentence method data and students’ writing skill data. The result of this research showed that based on SPSS calculation it was gained Asymp. Significance were 0,16 for X and 0,06 for Y. Then determination α = 0,5. If α > Asymp. Sig. (2-tailed) was not a normal distribution and If α < Asymp. Sig. (2-tailed) was Normal distribution in other words data distribution which was tested have normal distribution. Based on the homogeneity clculation it was If Fh < Ft therefore Ho was accepted. Fh(F-count) was 1.294366511 F Critical one-tail(F table) was 1.477376311. In short Fh was lower than F Critical. It means that it was homogen. The Coefience Correlation was compared with r Table. If Coefience Correlation > r Table, there was a significance correlation (Ha was accepted). If Coefience Correlation < r Table, there was a significance correlation (Ho was accepted). Based on the result was gained the significance value was 0,697, r table value with df 73 was 0,230. It means that Ha was accepted and there was a significance correlation between concept sentence method to students writing skill at the VII grade students of MTs Al-Khairiyah Pekalongan Cilegon academic year 2013/2014. Meanwhile R = 0,046. It means that correlation between variable X and variable Y was 0,046. To see the similarity regression significance could be seen from the value of F then compared with F Table. The conclusion was F = 1,52 and F Table = 1,47. Significance = 0,05. It means that F > F Table. Based on Anova formulation It could be used to predict of similarity regression. To make similarity regression was Constan = 75,862 X = 0,41. It means that similarity regression was Y = 75,862 + 0,41 X = 76,272